Lead isotope analyses from Tell Abraq, United Arab Emirates : new data regarding the 'tin problem' in Western Asia - Weeks, Lloyd
The 'tin problem' forms the focus for discussion on the earliest use of tin and bronze in western Asia and the Aegean. New research on lead isotope data from Tell Abraq in the UAE has important implications for the advent of bronze in the region.